Social Determinants of Health: Canadian Perspectives - Raphael, Dennis (Canadian Scholars' Press, 2025)
Now in its fourth edition, Dennis Raphael’s Social Determinants of Health offers the definitive Canadian discussion of the primary factors that influence the health of Canada’s population.This unique text on the social determinants of health contains contributions from top academics and high-profile experts from across Canada. Taking a public policy approach, the contributors to this edited collection critically analyze the structural inequalities embedded in our society and the socio-economic factors that affect health―including income, education, employment, housing, food security, gender, and race. This new edition includes recent statistics, new developments in early childhood education and the implementation of Canada’s national childcare system, and new content on the social determinants of Indigenous Peoples’ health. Particular attention is paid to how economic globalization and the acceptance of neoliberal governing ideology is shaping the health of Canadians. The COVID-19 epidemic vividly illustrated the importance of the social determinants of health, as sickness and death rates were strikingly higher among Canadians in groups already experiencing adverse living and working conditions and poorer health: lower income Canadians, recent immigrants of colour, and those experiencing housing and food insecurity. If anything positive is to come out of this experience, it will be recognition that in the current post-COVID-19 environment, it is essential to understand the socio-economic conditions that shape the health of individuals and communities. Social Determinants of Health, Fourth Edition is aimed at courses focusing on the social determinants of health at Canadian universities and colleges, particularly those in health studies and nursing, but also allied health, sociology, and human services. --Publisher's description